Changes in consumption behaviours of Polish seniors: Singles in 2007 and 2016 - Teresa Słaby (Economic and Environmental Studies (E&ES), 2019)
The increase in the share of the number of older people in the Polish population requires constant diagnosis of the degree of satisfying their needs. One of the ways of such assessment is the dynamic analysis of changes in the goods and services consumption. The author's research task was to find an answer to the question whether according to subjective opinions of seniors in 2007, there were consumption restrictions caused primarily by the deterioration of the their material situation and whether this situation deepened over the next 10 years. The aim of the article is to analyze the distribution of responses to this question in 2007 and 2016 based on the results of the GUS household budget surveys in single-person households (singles), where the situation may be particularly difficult. Two age groups were distinguished, differentiating the responses. The choice of years of observation was based on the occurrence of favourable assessments of the economic and social situations in these periods. One- and multi-dimensional tools of statistical analysis were used.
Keywords: D12; D14; D18; E21; 330; seniors 60; single-person households; consumption; expenses